Mitochondrial changes in carcinogenesis as a goal of antitumor therapy (review) - T. E. Potemina; E. V. Guzikov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2020)
Causes and mechanisms of cancer development are currently one of the urgent problems of medicine. The main variant for today is the mutation theory. Identification of the system of gene mutations, including in mitochondria, leading to this or that type of tumors, made it possible to develop a personalized, so-called targeting, the therapy of malignant tumors.